2000
DOI: 10.1542/peds.106.5.957
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Treatment of Neonates With Respiratory Failure and Group B Streptococcal Infection

Abstract: Surfactant therapy improves gas exchange in the majority of patients with GBS pneumonia. The response to surfactant is slower than in infants with RDS, and repeated surfactant doses are often needed. The mortality and morbidity are substantial, considering the relatively high mean birth weight of the treated infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(89 citation statements)
references
References 28 publications
0
79
0
9
Order By: Relevance
“…37 Exogenous surfactant therapy has been shown to be beneficial 70% of the time in patients with ARDS. 38 In a randomized, controlled trial using beractant in forty newborns with MAS, Findley et al 39 demonstrated a significant reduction in the need for extracorporeal membrane oxygenation (ECMO) therapy. Lotze et al 40 performed a large, multicenter study in 328 term newborns with ARDS secondary to MAS, sepsis-induced ARDS or persistent pulmonary hypertension.…”
Section: Surfactant Therapy and Nasal Continuous Positive Airway Presmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Exogenous surfactant therapy has been shown to be beneficial 70% of the time in patients with ARDS. 38 In a randomized, controlled trial using beractant in forty newborns with MAS, Findley et al 39 demonstrated a significant reduction in the need for extracorporeal membrane oxygenation (ECMO) therapy. Lotze et al 40 performed a large, multicenter study in 328 term newborns with ARDS secondary to MAS, sepsis-induced ARDS or persistent pulmonary hypertension.…”
Section: Surfactant Therapy and Nasal Continuous Positive Airway Presmentioning
confidence: 99%
“…38 Newborns with congenital diaphragmatic hernia (CDH) have been shown to have surfactant abnormalities. In a multicenter, randomized study, Anderson et al 43 demonstrated significant adverse outcomes among infants treated with surfactant.…”
Section: Surfactant Therapy and Nasal Continuous Positive Airway Presmentioning
confidence: 99%
“…It is interesting to speculate that a lack of DPPC inhibition of beta-h/c toxicity may in part explain the increased incidence and severity of GBS pneumonia and sepsis in premature, surfactant-deficient neonates (4). In the future, adjunctive therapies designed to neutralize beta-h/c could prove of use in management of neonatal GBS infections; indeed, surfactant therapy appears to exert a beneficial effect against pneumonia and lung injury produced by the organism (30). Neutralizing antibodies against the GBS beta-h/c do not develop as a consequence of natural infection nor have they been raised successfully to crude GBS beta-h/c preparations (31).…”
Section: Beta-hemolysin/cytolysinmentioning
confidence: 99%
“…60 Neonatal pneumonia Pneumonia in children and newborn infants may be associated with surfactant dysfunction and acute RDS. [61][62][63][64][65][66] There are studies involving a small number of neonates who have been treated with rescue surfactant replacement for sepsis and pneumonia that have shown improved gas exchange compared with no surfactant treatment. 61,63,64,67 -69 Verlato et al 70 used the 'exogenous' tracing approach with an endotracheal administration of 13 C-labeled DPPC to study surfactant kinetics in full term with pneumonia, and in preterms with RDS.…”
Section: Surfactant Status Of Preterm Infants Recovering From Rdsmentioning
confidence: 99%